2022
DOI: 10.7150/ijbs.70458
|View full text |Cite
|
Sign up to set email alerts
|

The role of Insulin-like growth factor 2 mRNA-binding proteins (IGF2BPs) as m6A readers in cancer

Abstract: RNA can be modified by over 170 types of distinct chemical modifications, and the most abundant internal modification of mRNA in eukaryotes is N6-methyladenosine (m 6 A). The m 6 A modification accelerates mRNA process, including mRNA splicing, translation, transcript stability, export and decay. m 6 A RNA modification is installed by methyltransferase-like proteins (writers), and potentially removed by demethylases (erasers), and this proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 197 publications
(225 reference statements)
1
25
0
Order By: Relevance
“…According to the literature, the IGF2BP protein family can bind m6A-modified mRNA and play an essential role in RNA stability [ 36 ]. Therefore, we used siRNA to knock down IGF2BP1/2/3 in the A2780 cell line and observed changes in SNAI1 mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, the IGF2BP protein family can bind m6A-modified mRNA and play an essential role in RNA stability [ 36 ]. Therefore, we used siRNA to knock down IGF2BP1/2/3 in the A2780 cell line and observed changes in SNAI1 mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, IGF2BP1 is capable of promoting BC distant metastasis (Figure 7C). IGF2BP1 is regarded as a classic RNA-binding protein involved in the regulation of gene expression [51,52]. Recent evidence has confirmed that IGF2BP1 can function as an m6A reader to recognize m6A sites and enhance targeted mRNA stability [23].…”
Section: Discussionmentioning
confidence: 99%
“…IGF2BPs influence gene regulation and cancer biology by enhancing the stability and storage of their target mRNAs. IGF2BP1 is a conserved oncogenic driver with significantly upregulated expression in various types of cancer ( 129 , 130 ).…”
Section: M6a and Ecmentioning
confidence: 99%